The Effect of Profitability, Firm Age, and The Independent Board of Commissioners to Corporate Social Responsibility Disclosure Listed on IDX - L, Lasonia Luxeya (Undergraduate Program in Accounting, Department of Accounting, Faculty of Economics and Business, Universitas Tanjungpura, 2021)
THE EFFECT OF PROFITABILITY, FIRM AGE, AND THE INDEPENDENT BOARD OF COMMISSIONERS TO CORPORATE SOCIAL RESPONSIBILITY DISCLOSURE LISTED ON IDXBy:Lasonia Luxerya LamonggaB1034171022Faculty of Economic and BusinessTanjungpura UniversityABSTRACTThis research was conducted to find out how the influence of profitability, firm age, and the independent board of commissioners to corporate social responsibility disclosure listed on the Indonesia Stock Exchange in 2015